Pelatihan Perawatan Jenazah dan Pendampingan Pendirian Lembaga Kematian Masjid At-Taqwa Perum Korpri, Tembalang, Semarang - Rohmat Suprapto; Ali Imron; Rochman Basuki (Universitas Muhammadiyah Semarang, 2024)
The At-Taqwa Mosque of Perum Korpri Bulusan Tembalang (service partner) is located in the RW 5 area of Bulusan Village, Tembalang District, Semarang City, which has considerable potential to be developed into a da'wah and social center. Apart from its geographical location surrounded by 6 housing estates, near the village and sub-district offices,. TheAt-Taqwa Perum Korpri Mosque has also played an active role as a place for social activities for the surrounding community. This Community Service aims to encourage the formation of Institutions / Pillars of Death and provide professional training to recruited staff to be ready at any time to care for the bodies of residents who have died. The method used is lecture, question and answer and direct practice. There was a significant increase in knowledge where prior to training on corpse care only 23.1% of the participants knew, while 76.9% did not know, 88.4% knew, and only 11.6% did not know. This shows that the method used is very effective.